2021
DOI: 10.1021/acs.jpcc.1c05891
|View full text |Cite
|
Sign up to set email alerts
|

Cation and Anion Transfer in Quinuclidinium Hexafluorophosphate Plastic Crystal: Role of Constituent Ions and the Crystalline Structure

Abstract: This research demonstrates the cation and anion transfer of an organic ionic plastic crystal (OIPC), quinuclidinium hexafluorophosphate ([HQ]­PF6), in the pure state and mixtures doped with lithium or chloride ions. The pure material and the mixtures show relatively simple thermal behaviors. Powder X-ray diffraction determined a cubic crystal structure, a common feature of OIPCs, in the high-temperature phase of the pure material. Solid-state nuclear resonance spectra of the pure material reveal rotation-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The transfer learning here corresponds to preserving fairness for a single sensitive attribute but over different tasks. However, Lan and Huan [17] found empirically that fairness does not transfer well to a new domain. They found that as accuracy increased in the transfer process, fairness decreases in the new domain.…”
Section: Domain Adaptation and Fairnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer learning here corresponds to preserving fairness for a single sensitive attribute but over different tasks. However, Lan and Huan [17] found empirically that fairness does not transfer well to a new domain. They found that as accuracy increased in the transfer process, fairness decreases in the new domain.…”
Section: Domain Adaptation and Fairnessmentioning
confidence: 99%
“…In these cases, a proxy of the sensitive attribute have been used [14], or researchers need very sample-efficient techniques [1,4]. For distant proxies, researchers have asked how well fairness transfers across attributes [17]. Here the sensitive attribute differs in the source and target domains.…”
Section: Introductionmentioning
confidence: 99%
“…The drying of the pure material and doped mixtures was performed as reported previously . In brief, the samples were dried thoroughly under a vacuum for at least 48 h at 50–70 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Then, the pellet was fixed between two stainless steel electrodes of a homemade conductance cell and isolated from air using several silicone-rubber flat gaskets. A self-designed aluminum barrel was used for heating and cooling the conductance cell assembly, as reported previously . The temperature of the sample was measured using a K-type thermocouple with an accuracy of 0.5 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Subsequently, the Wang group reported a Ni-catalyzed asymmetric reductive carboacylation of pendant alkene enabled by an elaborated t Bu-4-morpholinylPyrox ligand, providing various chiral oxindoles derivatives in up to 80% yield and up to 89% ee. 15 Nevertheless, the most commonly used chiral ligands in current reductive cross-coupling reactions limit to the well-developed scaffolds. In 2020, we disclosed an 8-quinolinyl imidazoline (8-Quinim) enabled Ni-catalyzed carbamoyl-alkylation of unactivated alkene for the unprecedented synthesis of chiral nonaromatic heterocycles, in which 8-Quinox ligand performed inferiorly in enantioselectivity control.…”
Section: Table 1 Substrate Scope Of Ni-catalyzed Enanti...mentioning
confidence: 99%